Pembuatan Video Pembelajaran bagi Guru SMP di Salatiga - Hayat, Muhammad Syaipul; Muhtarom, Muhtarom; Sutrisno, Sutrisno; Nuvitalia, Duwi (Pelita: Jurnal Pengabdian kepada Masyarakat, 2023)
Teacher professionalism always views doing something right and good (do the right thing and do it right). Consequently, he will always look for strategic and systematic ways in his learning process to create a conducive and enjoyable learning situation. This service activity aims to train and assist teachers in making learning videos with the Camtasia software. The service activity was attended by 36 teachers and was carried out for three days of activities. The training was carried out using an andragogy approach, which consisted of more demonstrations, questions and answers, and practice and mentoring. The training material is presented with more practice than theory, with a 25% theory to 75% practice ratio. The success of the training was demonstrated by increasing participants' understanding regarding the use of the Camtasia software in making learning videos. The results of the questionnaire showed that there was an increase in participants' understanding of video making and learning video editing techniques. This is indicated by a visible increase in the mean pretest score of 57.78, which increased to 92.83 during the posttest. Meanwhile, the ability to create media was demonstrated by the fact that as many as 20 training participants had made learning video products. This means that service activities increase teacher skills in learning video media.